Text in Image Hiding using Developed LSB and Random Method - Elaf Ali Abbood; Rusul Mohammed Neamah; Shaymaa Abdulkadhm (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Information Hiding is a task that face difficult challenges in current time. The reason for these challenges is the rapid development of methods of detection of hidden information. So, researchers have been interested in developing methods of concealment, making it difficult for attackers to access hidden information using new methods of concealment. Such as the introducing a complex algorithms, use a random methods and invent more complicated and difficult steps. This paper presents a new method of hiding information within the image. This method creates a new sequence of mysterious and difficult steps by dividing the secret text on all image and random distributing of bits to each row. Then using a special reverse method to hide the bits in that row. The LSB method has also been developed to make it more difficult to hide the pixel. The results presented illustrate the strength and security of the method and provide greater protection for hidden information. Also, the result illustrate the quality of the stego image compared with the original image using PSNR and SSIM quality measures.